В решении.
Объяснение:
с -3 -2 -1
2с +3 2*(-3)+3= -3 2*(-2)+3= -1 2*(-1)+3 = 1
2(с+3) 2*(-3+3)=0 2*(-2+3)=2 2*(-1+3)=4
(2с)²-3 (2*-3)²-3=33 (2*-2)²-3=13 (2*-1)²-3=1
2(с²-3) 2*((-3)²-3)=12 2*((-2)²-3)=2 2*((-1)²-3)= -4
с 0 1 2 3
2с+3 0+3=3 2*1+3=5 2*2+3=7 2*3+3=9
2(с+3) 2*(0+3)=6 2*(1+3)=8 2*(2+3)=10 2*(3+3)=12
(2с)²-3 (2*0)²-3= -3 (2*1)²-3=1 (2*2)²-3=13 (2*3)²-3=33
2(с²-3) 2*(0²-3)= -6 2*(1²-3)= -4 2*(2²-3)=2 2*(3²-3)=12
I. 1) 5³ + 2⁴ = 125 + 16 = 141
2) (-7)² - (-2)² = 49 - 4 = 45
3) 6 * (-5/6)² = 6 * 25/36 ≈ 4,16
II. 1) m⁴ * m⁶ = m¹⁰
2) x * x⁷ = x⁸
3) a² * a¹⁶ = a¹⁸
4) a⁶ * a⁶ = a¹²
5) y * y⁹ * y⁴ = y¹⁴
6) c³ * c² * c⁸ = c¹³
7) (m + 2n)¹⁰ * (m + 2n) = (m + 2n)¹¹
8) z⁵ * z² * z * z¹¹ = z¹⁹
III. 1) a¹⁵ : a⁴ = a¹¹
2) c⁹ : c = c⁸
3) b⁸ : b⁸ = 1
4) (a - b)¹² : (a - b)⁶ = (a - b)⁶
IV. 1) a⁵ * a¹⁴ = a¹⁹
2) a⁴ * a * a² = a⁷
3) a⁹ : a⁴ = a⁵
4) a⁴² : a¹⁰ = a³²
5) a¹⁴ : a¹² * a⁹ = a¹¹
6) a¹⁸ * a⁷ : a²³ = a²
V. 1) 3⁴ * 3⁵ = 3⁹ = 19683
2) 2⁵ * 2² = 2⁷ = 128
3) 5¹¹ * 5⁷ : 5¹⁵ = 5³ = 125
4) 29¹⁰ * 29⁶ : 29¹⁴ = 29² = 841
x²−2xy+y²=(-9,5)²-2·(-9,5)·(-2,7)+(-2,7)²=90,25-51,3+7,29=46,24
-(x−y)²=(-9,5-(-2,7))²=(-6,8)²=46,24